3D printing technology in orthodontics – review of current applications - Bartkowiak, Tomasz; Walkowiak-Śliziuk, Agata (Journal of Stomatology, 2018)
Additive manufacturing is a relatively new technology with rapidly growing range of applications in many fields of medicine and dentistry. The developments of available computer-aided design software and additive manufacturing hardware allowed integrating the technology in orthodontics, and revolutionizing the workflow in orthodontic practices and laboratories around the world. 3D printing is now easily accessible for orthodontists, being a reliable and cost-effective manufacturing method, which may be used in many aspects of orthodontic practice, and its potential is still growing. The article gives necessary insight into the history, development, and available technologies of additive manufacturing. Moreover, it summarizes and reviews current literature concerning all aspects of clinical use of 3D printing in orthodontics.